Efektifitas Pemasaran Digital Untuk Komoditas Beras Sebagai B2C (Business To Consumer) Dalam Rangka Mendukung Ketahanan Pangan Indonesia - Chriswardana Bayu Dewa; Lina Ayu Safitri; Diah Pradiatiningtyas; R Jatinurcahyo (Jurnal Akuntansi dan Pajak, 2025)
Food security concerns several aspects to ensure that people's food needs are met, namely availability, access, safety, diversity and quality of food and nutrition. Rice distribution channels also exist in every region which are managed by government agencies. However, in the middle of 2023 there will be instability in grain prices due to a long drought. This causes rice entrepreneurs, especially selepan, to be hesitant to distribute rice stocks to wholesalers due to changes in grain prices that occur every hour. This condition has resulted in Selepan rice entrepreneurs choosing to sell rice directly to retailers and final consumers so that financial flows remain stable. Technological developments have brought business development in a positive direction. One of them is for business people developing B2C digital marketing for rice commodities. The use of digital marketing in marketing cases helps to increase customer knowledge according to their needs. This research uses a quantitative design. Data were collected using observation, interviews with rice entrepreneurs by observing the distribution flow of rice from rice entrepreneurs and rice mills in Duwet Klaten Village, Central Java until it reaches consumers. The research results show that the use of Instagram and WhatsApp is an efficient and relevant digital marketing strategy, especially for small and medium businesses such as Harkes Rice Mill and BMG in Klaten. This platform not only allows rice mills to reach a wider range of consumers, but also provides a more personalized, effective and cost-effective transaction experience to support Indonesia's food security.